2010
DOI: 10.1038/cdd.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PK promotes the survival of young neurons in the embryonic mouse retina

Abstract: Programmed cell death is a crucial process in neural development that affects mature neurons and glial cells, as well as proliferating precursors and recently born neurons at earlier stages. However, the regulation of the early phase of neural cell death and its function remain relatively poorly understood. In mouse models defective in homologous recombination or nonhomologous end-joining (NHEJ), which are both DNA double-strand break (DSB) repair pathways, there is massive cell death during neural development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…Persistence of phosphorylation of H2AX in Nbn/Atm-deficient retina strongly suggest that at least one alternative kinase, is able to phosphorylate H2AX independently of both Nbn and Atm in RPC. It has been proposed that DNA-PKcs may regulate retinal development [51]. In addition, after analyzing the distribution of all retinal cell types right after the vast majority of RPC have become post-mitotic (P9), we provide evidence that cell fate specification or early steps of cell differentiation of retinal neurons and glia are not affected by Nbn and/or Atm deficiency.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Persistence of phosphorylation of H2AX in Nbn/Atm-deficient retina strongly suggest that at least one alternative kinase, is able to phosphorylate H2AX independently of both Nbn and Atm in RPC. It has been proposed that DNA-PKcs may regulate retinal development [51]. In addition, after analyzing the distribution of all retinal cell types right after the vast majority of RPC have become post-mitotic (P9), we provide evidence that cell fate specification or early steps of cell differentiation of retinal neurons and glia are not affected by Nbn and/or Atm deficiency.…”
Section: Discussionmentioning
confidence: 74%
“…We suggest that ATR may be the kinase responsible for γ-H2AX, since Nbn has been shown to be dispensable for ATR mediated H2AX phosphorylation [52]. Nevertheless, it is not possible to exclude DNA-PKcs since it may compensate Atm loss in an efficient way and it was also shown to play a role in the survival of neural cells [51], [54][56]. In dividing cells, during the first part of the embryonic development, the DSBs trigger a survival signal, through the activation of cell cycle checkpoint mediated by p53 and others.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, it was found that most of the apoptotic cell death in mice harboring a homozygous hypomorphic mutation in LIG4 (LIG4 Y288C) occurs in the intermediate zone, which contains nonreplicating differentiated neurons [258]. In a study using a mouse model for neuroretina, small molecule inhibition of DNA-PK results in the death of neurons isolated from embryos at day 14.5, suggesting a role for NHEJ in early retinal neurogenesis [259]. In the case of DNA-PKcs-deficient mice, however, they exhibit no obvious neuropathology, suggesting normal neurogenesis in the brain [260].…”
Section: Dna Repair Pathwaysmentioning
confidence: 99%
“…Among other possible intrinsic cell death determinants, the generation and repair of DNA double-strand breaks have been consistently associated with neural cell death and may underlie the induction of cell death and the generation of phenotypic diversity. Indeed, we previously reported that in SCID mutant mice, in which DNA repair is compromised, RGCs selectively undergo extensive cell death [23]. Although the existence of somatic mosaicism in the nervous system was proposed over 30 years ago [24], recent studies combining neural stem cells, single cell analysis, and ultrasequencing approaches have allowed for a much more detailed analysis than previously possible.…”
Section: Discussionmentioning
confidence: 99%